The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1745-6215-13-41
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous magnesium prevents atrial fibrillation after coronary artery bypass grafting: a meta-analysis of 7 double-blind, placebo-controlled, randomized clinical trials

Abstract: BackgroundPostoperative atrial fibrillation (POAF) is the most common complication after coronary artery bypass grafting (CABG). The preventive effect of magnesium on POAF is not well known. This meta-analysis was undertaken to assess the efficacy of intravenous magnesium on the prevention of POAF after CABG.MethodsEligible studies were identified from electronic databases (Medline, Embase, and the Cochrane Library). The primary outcome measure was the incidence of POAF. The meta-analysis was performed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 33 publications
2
48
2
1
Order By: Relevance
“…Perioperative hypomagnesaemia is associated with different forms of cardiac arrhythmias, particularly with atrial fibrillation [8,11,12]. Magnesium stabilizes mitochondrial ion transport and calcium channel activity improving the cellular bioenergic status, which prevent abnormal pacemaker activity [1,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative hypomagnesaemia is associated with different forms of cardiac arrhythmias, particularly with atrial fibrillation [8,11,12]. Magnesium stabilizes mitochondrial ion transport and calcium channel activity improving the cellular bioenergic status, which prevent abnormal pacemaker activity [1,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Intra-cardiac Mg reduces β-adrenergic stimulation [13], and interestingly, a 7% reduction of intra-cardiac Mg increases 5-fold the multivariate risk of postoperative atrial fibrillation in patients undergoing CABG [15]. For this reason, several authors have proposed perioperative infusion of Mg as a prophylactic treatment of post-operative cardiac arrhythmia [8,11,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, several small-scale studies have examined the effect of Mg 2ϩ in preventing these fibrillations (93). Meta-analysis of these studies concluded that Mg 2ϩ infusion may prevent atrial fibrillations (201,474). Therefore, the European Association for Cardiothoracic Surgery and the Canadian Cardiovascular Society recommend prophylaxis with intravenous MgSO 4 .…”
Section: Arrhythmiamentioning
confidence: 99%
“…Investigations of Mg prophylaxis for the prevention of POAF in the context of cardiac surgery appeared to confirm these beneficial results. [18][19][20][21] However, several of these studies were limited by small sample size, improper blinding, and the use of a lower dose of Mg than in the current study. In fact, by combining studies on Mg prophylaxis in CABG surgery that were properly blinded and with sufficient patient sample sizes, Hazelrigg et al 34 failed to find an overall reduction in postoperative atrial or ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, the administration of Mg may attenuate sympathoadrenal-mediated arrhythmias. 16,17 While several trials and meta-analyses have suggested a beneficial effect of Mg administration in preventing POAF, [18][19][20][21] many of these studies were limited by small sample size, relatively low Mg dosage, and an inability to account for concomitant medications known to influence POAF. We hypothesized that high-dose Mg decreases the occurrence of new-onset POAF, and we tested this hypothesis using data from a prospective trial assessing the effect of Mg on cognitive outcomes in patients undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%